Prevalence and correlates of influenza-a in piggery workers and pigs in two communities in Lagos, Nigeria (2013)
Introduction: Worldwide, three Influenza-A virus subtypes (H1N1, H1N2 and H3N2) in swine are major public health issues. In Nigeria, the existence of these subtypes in pigs has not been well studied. This study aimed at determining the prevalence and correlates of Influenza-A viruses circulating in piggery workers and pigs in Oke-aro and Goshen communities in Lagos, Nigeria. Methods: Nasal swabs were taken from 197 consenting piggery workers and 281 randomly selected pigs to determine the prevalence of Influenza-A (H1, H3, H5) using Reverse Transcriptase Polymerase Chain Reaction test (gene M). An interviewer administered questionnaire was used to collect information on demography, Influenza-A related symptoms experienced, personal hygiene and management practices from the piggery workers. Descriptive statistics was used and chi square test performed at 5% significant level. Results: All piggery workers and pigs' nasal swabs tested negative for Influenza-A viruses, hence, association could not be tested. Mean age of piggery workers was 41 ± 13.6 years and 60% were females. Forty two percent were farm attendants, 38.0% were pig farmers and the rest butchers. Nineteen percent had history of headache; 14.0% had catarrh and cough; 4.0% had sore-throat; 5.0% had diarrhea; while 48.0% had muscle pain at the time of data collection. The mean body temperature for the pig workers was 36.5 ± 0.5 °C. A significant difference (p<0.05) existed among piggery workers who had muscle pains. Conclusion: Piggery workers and pigs in study area were free of Influenza-A (H1, H3, H5) viruses. The current practices of the piggery workers should be encouraged.